GBR assisted in situ Onlay bone grafting for the posterior mandible horizontal ridge augmentation: a case report and literature review - Li, Mucong; Liu, Xiuyu; Zhou, Jing; You, Jiaqian; Chen, Sheng; Feng, Jian; Wei, Xuyan; Wang, Hanchi; Zhou, Yanmin (Frontiers in Bioengineering and Biotechnology, 2025)
The posterior mandible is the primary area for occlusal function. However, long-term tooth loss in the posterior mandible often leads to rapid absorption of both buccal and lingual trabecular bone plates and subsequent atrophy of the alveolar ridge. This ultimately results in horizontal bone deficiencies that complicate achieving an optimal three-dimensional placement for dental implants. Conventional techniques employed clinically for horizontal bone augmentation have limited efficacy, cause significant surgical trauma, and require extended treatment duration. Consequently, the selection of an effective and minimally invasive bone augmentation technique for restoring bone width is an essential prerequisite for successful implant restoration in the posterior mandible. This clinical case study presented a treatment approach involving guided bone regeneration (GBR) and in situ Onlay grafting for bone level augmentation in the blade-shaped alveolar ridge of the posterior mandible, followed by implant restoration. By rotating the in situ sourced bone block, the denser bone volume at the base of the blade-shaped alveolar ridge was transferred to the crest of the alveolar ridge, obviating the necessity for a secondary operative site and mitigating complications such as pain, edema, sensory abnormalities, and nerve injury. Incorporation of trabecular bone within the recipient area enhanced fixation while augmenting vascular supply. A significant increase in bone volume by 1,628.21 mm3 was achieved within 7 months postoperatively. Overall, this novel approach offers valuable insights into minimally invasive and stable techniques for alveolar bone augmentation.